Intraoperative transcutaneous electrical acupoint stimulation combined with anesthesia to prevent postoperative cognitive dysfunction: A systematic review and meta-analysis - Lin Gan; Kecheng Qian; Jinding Yang; Qian Cai; Qinyu Ye; Mengyuan Dai; Zhaoxing Jia; Tianxiang Jiang; Congcong Ma; Xianming Lin (PLoS ONE, 2025)
Background Postoperative cognitive dysfunction (POCD) is associated with an increased risk of dementia and may lead to chronic neurodegeneration. The utilization of intraoperative Transcutaneous Electrical Acupoint Stimulation (TEAS) in conjunction with anesthesia is expected to become an effective preventive measure for POCD in clinical practice. Methods We conducted a comprehensive literature review focusing on the use of TEAS in the prevention of POCD during surgical anesthesia. We searched various databases for relevant literature, including PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), and Wanfang Data. The synthesis of data was performed using RevMan version 5.4. Results Our meta-analysis incorporated data from 20 Randomized Controlled Trials (RCTs) involving 1549 patients. The findings revealed that intraoperative TEAS significantly reduced the incidence of POCD when compared to the control group [Odds Ratio (OR) 0.29, 95% Confidence Interval (CI) 0.22–0.39, p < 0.00001]. Moreover, patients receiving intraoperative TEAS exhibited a significant increase in MMSE scores (MD 1.21, 95% CI 0.53–1.89, p = 0.0005). Additionally, intraoperative TEAS demonstrated efficacy in reducing the contents of perioperative serum S100β protein (S100β), neuron-specific enolase (NSE), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) in patients, and the improvement of these indexes may be the potential mechanism of TEAS in preventing POCD. Conclusion Our results suggest that intraoperative TEAS combined with anesthesia prevents cognitive dysfunction in the immediate postoperative period, however we need additional evidence of its utility in preventing long-term cognitive dysfunction. We advocate for the broader promotion and application of this approach in clinical surgical settings. Trial registration PROSPERO (CRD42023457910).